Effects of Release Modifier and Annealing on Polyvinyl Acetate-Polyvinyl Pyrrolidone Microspheres Containing Diclofenac Sodium - Islam, Md. Saiful; Jalil, Reza-ul (Dhaka University Journal of Pharmaceutical Sciences, 2013)
This study was conducted to microencapsulate water soluble diclofenac sodium (DS), a potent NSAID advocated for use in painful, inflammatory, and certain non-rheumatic conditions. To modify its release pattern, polyvinyl acetate-polyvinyl pyrrolidone based matrix polymer, Kollidon ® SR (KSR) was used as wall material. Microspheres were prepared by water-in-oil (W/O) emulsion solvent evaporation technique using KSR while maintaining core to polymer ratio at 1:1. Two release modifiers namely polyethyleneglycol 6000 (PEG 6000) and talc at four different concentrations (3%, 5%, 10% and 15% wt/wt of the wall material) were used to investigate their effect on microsphere properties and release kinetics of the drug. Optimized batches were characterized according to particle size distribution, surface morphology, differential scanning thermogram, and in vitro release of the drug. In vitro dissolution study was conducted in phosphate buffer solution of pH 7.2 for 8 hours. Microsphere sizes were within the range of 497-922?m. No interaction between drug and excipients was observed. Characteristic changes in the microsphere surface were observed due to the presence of PEG 6000 and talc. All optimized batches showed good controlled release property with immediate burst release. Annealing (heating the microspheres at 60°C for 24 hours) was found effective in controlling the immediate burst release of the drug. Case I or fickian-type release mechanism was found predominant in case of all formulated microspheres. Dhaka Univ. J. Pharm. Sci. 12(1): 41-50, 2013 (June) DOI: http://dx.doi.org/10.3329/dujps.v12i1.16299